Adaptive Esports for People With Spinal Cord Injury: New Frontiers for Inclusion in Mainstream Sports Performance - Tabacof, Laura; Dewil, Sophie; Herrera, Joseph E.; Cortes, Mar; Putrino, David (Frontiers in Psychology, 2021)
Introduction: People with Spinal Cord Injury (SCI) are at risk of feeling socially disconnected. Competitive eSports present an opportunity for people with SCI to remotely engage in a community. The aim of this study is to discuss barriers to eSports participation for people with SCI, present adaptive solutions to these problems, and analyze self-reported changes in social connection. Materials and Methods: We presented a descriptive data collected in the process of a quality improvement initiative at Mount Sinai Hospital. In 2019, seven individuals with cervical SCI and quadriplegia participated in a special interest group on eSports. Group scores were then analyzed for evidence of between subjects variability using a single sample t-test. A Pearson’s correlation was conducted to determine the relationship between social connectedness and demographic data. Results: All players experienced functional limitations as a result of their injury but managed to design personalized gaming setups with adaptive equipment that allowed them to successfully compete in eSports. All players reported a positive change in perceived social connectedness (p<0.001) after participating in the special interest group. Score on Social Connectedness Scale negatively correlated with Time since injury (years). Discussion: It is feasible to create adaptive gaming setups that can be used by people with differing degrees and severity of SCI in a competitive eSports environment. Technology and adaptive competitive eSports have a potential to improve social connectedness and inclusion in people with quadriplegia. Further research on efficacy and effectiveness of these inclusive environments and their effects on quality of life, activity and participation is warranted.